2011
DOI: 10.1093/nar/gkr934
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Cyclin B1 by miRNA and its implications in cancer

Abstract: It is largely recognized that microRNAs (miRNAs) function to silence gene expression by targeting 3′UTR regions. However, miRNAs have also been implicated to positively-regulate gene expression by targeting promoter elements, a phenomenon known as RNA activation (RNAa). In the present study, we show that expression of mouse Cyclin B1 (Ccnb1) is dependent on key factors involved in miRNA biogenesis and function (i.e. Dicer, Drosha, Ago1 and Ago2). In silico analysis identifies highly-complementary sites for 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
255
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(266 citation statements)
references
References 62 publications
10
255
1
Order By: Relevance
“…24,25 Most recently, cyclinB1 was shown to be upregulated by miR-744 and miR-1186, prolonged overexpression of which causes CIN and inhibits tumour growth. 26 Central to mitosis is SAC, which monitors accurate chromosome segregation. Although Mad1, Mad2, BubR1/Mad3 and Bub3 are major SAC components, they have been joined by players like Cdc20, Bub1, Mps1 and AuroraB.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Most recently, cyclinB1 was shown to be upregulated by miR-744 and miR-1186, prolonged overexpression of which causes CIN and inhibits tumour growth. 26 Central to mitosis is SAC, which monitors accurate chromosome segregation. Although Mad1, Mad2, BubR1/Mad3 and Bub3 are major SAC components, they have been joined by players like Cdc20, Bub1, Mps1 and AuroraB.…”
Section: Discussionmentioning
confidence: 99%
“…A number of documentation showed that, less RNAPII (RNA polymerase II) is available at promoter region after TGS [40,42,44,[46][47][48][49][50][51] where as there is an enrichment of RNAPII in case of RNA [50,[52][53][54]. Studies have reported modified histones enriched promoters having well known silencing marks after TGS and active marks just after RNAa.…”
Section: Argonate Protein In Transcription Machinery and Epigenetic Rmentioning
confidence: 99%
“…Nuclear function of AGO proteins also reported as a regulator of transcriptional gene silencing (TGS) in fission yeast and plants. Nuclear role of mammalian AGO proteins include gene activation [52,60,65], TGS [57,[66][67][68] and alternative splicing [64] (Figure 3). AGO1 and AGO2 both play an important role in neuronal differentiation by miRNA-mediated process [69] through binding with the same pool of miRNAs and mRNA targets [70].…”
Section: Argonate Protein In Transcription Machinery and Epigenetic Rmentioning
confidence: 99%
See 2 more Smart Citations